2012
DOI: 10.1039/c2cc31636f
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of reduced graphene oxides by redox-active ionic liquids for energy storage

Abstract: The reduced graphene oxides (RGOs) functionalized by pyridinium-based ionic liquids (ILs) with SCN anions revealed 6-fold higher capacitance compared to that of RGOs due to the redox behavior of ILs as well as good rate capability and cycle stability despite the appearance of pseudo-capacitance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…1) As proven by the linear dependence of capacitive peak currents on scan rates, [21] the surface-confined electrochemistry of RHEs implies that pseudocapacitive charging/discharging was triggered by a reversible redox transition of electroactive quinone moieties confined on the surface of RHEs (Figure 3 a and a1). The surface confinement of Lig nanocrystals on RHEs was verified by TEM analysis.…”
Section: Resultsmentioning
confidence: 91%
“…1) As proven by the linear dependence of capacitive peak currents on scan rates, [21] the surface-confined electrochemistry of RHEs implies that pseudocapacitive charging/discharging was triggered by a reversible redox transition of electroactive quinone moieties confined on the surface of RHEs (Figure 3 a and a1). The surface confinement of Lig nanocrystals on RHEs was verified by TEM analysis.…”
Section: Resultsmentioning
confidence: 91%
“…It is concluded that the C carbon value for RGO is much larger than those for CB and SWNT, as also reported previously. 24,25,[40][41][42] The POM/RGO nanohybrid materials, in which the weight ratio of TBA 3 [POM] was 33 wt%, were prepared by using the same method as that previously reported for the POM/SWNT nanohybrid materials. 12,14 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Especially during the discharge process, contrary to h‐TiN, the R ct of m‐TiN sharply increases as soluble LiPS are reduced to the insulating solid phase (Li 2 S 2 /Li 2 S) at 2.0 and 1.7 V. The severe increase in R ct in this region is well matched with the low D Li value of m‐TiN in peak II. During the charge process, the Warburg's slope of h‐TiN is steeper than that of m‐TiN, indicating that the fast Li + ion movement and low R d in h‐TiN was promoted by the macropore . Furthermore, the R e of h‐TiN is higher than that of m‐TiN at the beginning of the discharge process, but is lower than that of m‐TiN (3.0 vs 10.0 Ω) at the end of the charge process.…”
mentioning
confidence: 93%